Germans into Jews : remaking the Jewish social body in the Weimar Republic - Gillerman, Sharon, 1960- (Stanford studies in Jewish history and culture., 2009)
Germans into Jews turns to an often overlooked and misunderstood period of German and Jewish history--the years between the world wars. It has been assumed that the Jewish community in Germany was in decline during the Weimar Republic. But, Sharon Gillerman demonstrates that Weimar Jews sought to rejuvenate and reconfigure their community as a means both of strengthening the German nation and of creating a more expansive and autonomous Jewish entity within the German state.